Analisis hasil pengukuran Key Performance Indikator Ratio Produksi dengan Sigma level dan DPMO - Supriyati, Supriyati; Irwati, Dwi; Hermawan, Muhid; Nurlaili, Nurlaili (JURNAL TEKNIK INDUSTRI, 2022)
SAn established company has a goal to produce products and services. To determine the company's performance in terms of quality and other KPI’s as measurement indicators are applied in the company. One way to measure organizational achievement with KPI to be more accurate is to use the SMART method. The expectation of a company that implements KPI is the optimal achievement of the specified target even though the implementation of several components has not been achieved. Production Ratio is one of the company's KPIs, some Plants have not met the expected expectations. There are 4 production plants, 3 plants did not reach the target, from the results of data processing Plant 1 has the highest DPMO value and the lowest Sigma when compared to other plants, process variations and product types affect quality and have an impact on KPI achievement.